Innovation of the Teacher's Standby Guidebook in Elementary Schools as an Effort to Prepare for Disaster-Safe Education: Qualitative Perspective - Hartatik, Rida; Poerwanti, Endang; Zuriah, Nurul; Tinus, Agus (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Elementary schools in disaster-prone regions play a crucial role in instilling disaster awareness and preparedness skills at an early age. This study aimed to develop the Guru Siaga Guidebook as an innovation to support the Satuan Pendidikan Aman Bencana (SPAB) program in Ngantang District, Malang Regency. Using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), integrated with qualitative insights from interviews, observations, and user feedback, data were collected through surveys, interviews, observations, and expert validation. The analysis revealed that most schools lacked structured disaster preparedness procedures, contextual learning materials, and routine simulations. Teachers and students expressed the need for a practical, engaging, and context-specific guidebook. The developed product included modules on disaster introduction, mitigation, evacuation, and first aid, complemented by visuals and interactive activities. Validation by material and media experts rated the guidebook as feasible and relevant (Material S-CVI/Ave = 0.89; Media S-CVI/Ave = 0.86). Field trials involving nine teachers and 90 students showed increased teacher preparedness scores (from 62.3 ± 8.4 to 74.9 ± 7.2; Cohen’s d = 0.64) and improved student accuracy in evacuation steps (from 68% to 83%). Findings provide preliminary evidence that the guidebook supports disaster education and enhances preparedness indicators, aligning with national and international frameworks for safe schools. The guidebook introduces three distinctive features: localized hazard case studies, project-based evacuation drills with assessment rubrics, and child-friendly SOP flowcharts.